Towards S²-Challenges Underlying LLM-Based Augmentation for Personalized News Recommendation - Wang, Shicheng; Tang, Hengzhu; Gao, Li; Guo, Shu; Cheng, Suqi; Wang, Junfeng; Yin, Dawei; Liu, Tingwen; Wang, Lihong (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Personalized news recommendation aims to recommend candidate news to the target user. Since the data and knowledge involved in traditional recommender systems are restricted, recent studies utilize large language models (LLMs) to generate news articles and augment the original dataset. However, despite the superiority of LLM-based augmentation in news recommendation, previous studies still suffer from two serious problems, i.e., structure-level deficiency and semantic-level noise. Since the LLM-based augmentation is mainly implemented at the semantic level, collaborative signals, the critical structure information in recommender systems, is neglected during the generation process. Thus, it is inappropriate to perform recommendation based on the augmented user-news bipartite, which manifests as multiple isolated cliques. Moreover, utilizing the open-world knowledge of LLMs to extend the closed systems will inevitably introduce noise information, leading to difficulties in mining users' real preferences. In this paper, we propose a novel Structure-aware and Semantic-aware approach for LLM-Empowered personalized News Recommendation, named S^2LENR, to tackle the mentioned problems. Specifically, we propose a structure-aware refinement module to inject collaborative information in a parametric way, in order to construct a valid augmented bipartite. Besides, we devise a semantic-aware denoising module utilizing contrastive learning paradigm to overcome the negative effects of noise information. Finally, we calculate the relevance score between target user and candidate news representations. We conduct experiments on two real-world news recommendation datasets MIND-Large, MIND-Small and empirical results demonstrate the effectiveness of our approach from multiple perspectives.